Intraventricular hydatid cyst in a child - Kamath Sulata; Mysorekar Vijaya; Rao Saraswathi; Varma Ravi (Wolters Kluwer Medknow Publications, 2009)
Hydatid disease is caused by the infestation of the larvae of tapeworms of the genus Echinococcus. The definitive hosts of Echinococcus are various carnivores, the common being the dog. All mammals (more often sheep and cattle) are intermediate hosts. Humans get infected through the feco-oral route by ingestion of food or milk contaminated by dog feces containing ova of the parasite or by direct contact with dogs. The most common sites of infestation are the liver (75%) and lungs (15%). Various authors state a frequency of hydatidosis of the brain ranging between only 0.2-4% of cases. [1],[2],[3] The prognosis following surgical intervention is good, especially in pediatric age. [2],[3] Hence early diagnosis of this condition is crucial. We report a rare case of a child with a large intraventricular hydatid cyst that had an excellent recovery following surgery.